2001
DOI: 10.1074/jbc.m011708200
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 3 (UCP3) Stimulates Glucose Uptake in Muscle Cells through a Phosphoinositide 3-Kinase-dependent Mechanism

Abstract: UCP3 is a mitochondrial membrane protein expressed in humans selectively in skeletal muscle. To determine the mechanisms by which UCP3 plays a role in regulating glucose metabolism, we expressed human UCP3 in L6 myotubes by adenovirus-mediated gene transfer and in H 9 C 2 cardiomyoblasts by stable transfection with a tetracycline-repressible UCP3 construct. Expression of UCP3 in L6 myotubes increased 2-deoxyglucose uptake 2-fold and cell surface GLUT4 2.3-fold, thereby reaching maximally insulin-stimulated lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 51 publications
1
60
0
2
Order By: Relevance
“…However, the uncoupling of yeast mitochondria by mammalian UCP3 (6, 7, 11-13) is an expression artifact (13, 15-18) that provides no evidence for a physiological uncoupling function in mammalian cells. Uncoupling following UCP3 expression in transgenic mammalian systems (9,30,50) may also be an expression artifact that provides no evidence for physiological uncoupling by UCP3, as shown for the uncoupling of mouse skeletal muscle in UCP3-tg mice in the present paper. Experiments in which UCP3 concentrations have been changed by physiological manipulations (19 -27), and the lack of effect of UCP3 knockout on whole animal energy metabolism and basal metabolic rate (31,32) despite the importance of muscle proton leak to physiological energetics (49), support the conclusion that UCP3 is not a significant contributor to the basal proton conductance of muscle mitochondria.…”
Section: Figmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the uncoupling of yeast mitochondria by mammalian UCP3 (6, 7, 11-13) is an expression artifact (13, 15-18) that provides no evidence for a physiological uncoupling function in mammalian cells. Uncoupling following UCP3 expression in transgenic mammalian systems (9,30,50) may also be an expression artifact that provides no evidence for physiological uncoupling by UCP3, as shown for the uncoupling of mouse skeletal muscle in UCP3-tg mice in the present paper. Experiments in which UCP3 concentrations have been changed by physiological manipulations (19 -27), and the lack of effect of UCP3 knockout on whole animal energy metabolism and basal metabolic rate (31,32) despite the importance of muscle proton leak to physiological energetics (49), support the conclusion that UCP3 is not a significant contributor to the basal proton conductance of muscle mitochondria.…”
Section: Figmentioning
confidence: 81%
“…Proton leak in muscle is a significant contributor to standard metabolic rate (49), and modulation of mitochondrial proton conductance in muscle constitutes a mechanism of regulation of energy dissipation and standard metabolic rate. Whether the uncoupling caused by transfection of UCP3 into myotubes and cardiac muscle cells (50) or by transgenic expression of UCP1 in mouse muscle (47) is a result of native function of the UCPs or an expression artifact remains to be determined by direct tests of the GDP and superoxide sensitivity of mitochondria isolated from the relevant cells.…”
Section: Figmentioning
confidence: 99%
“…UCP3 is best known for its roles in promoting fatty acid oxidation (MacLellan et al 2005) and limiting mitochondrial damage by suppression of lipid peroxidation and the production of reactive oxygen species (Vidal-Puig et al 2000, Brand et al 2002. But, UCP3 can also stimulate glucose uptake and recruitment of SLC2A4 to the cell surface (Huppertz et al 2001) and so its decline in programmed offspring may contribute to the observed accumulation of cytoplasmic SLC2A4. Interestingly, reduced skeletal muscle Ucp3 expression has also been observed in diabetic human subjects (Krook et al 1998, Schrauwen et al 2001, and a recent report indicates that this is already the case in prediabetic subjects with impaired glucose tolerance (Schrauwen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The skeletal muscle expression of SLC2A4 mRNA and protein, including its subcellular localization, and peroxisome proliferator-activated receptor (PPAR)-d, PPAR-g coactivator-1a (PPARGC1A), and uncoupling protein 3 (UCP3) mRNAs, were also determined. These genes were targeted because PPARD is a key regulator of fuel metabolism (Brunmair et al 2006), the effects of which involve coactivation by PPARGC1A (Finck & Kelly 2006), whereas UCP3 promotes fatty acid oxidation (MacLellan et al 2005) and glucose uptake (Huppertz et al 2001), and limits mitochondrial damage via effects on lipid peroxidation (Brand et al 2002). The interactive effects of a postnatal, high u-3 fatty acid (high n-3, Hn3) diet were also determined, since our previous studies show that this dietary intervention markedly reduces other adverse phenotypic outcomes programmed by fetal glucocorticoid excess (Wyrwoll et al 2006(Wyrwoll et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of L6 myotubes with the strong chemical uncoupler dinitrophenol stimulated glucose uptake (3). Recently, Huppertz et al (15) showed that overexpression of UCP3 in L6 myotubes increases glucose uptake through increased recruitment of GLUT4 to the cell surface. Overexpression of UCP3 in transgenic mice resulted in increased glucose tolerance and reduced fasting plasma glucose levels (2).…”
mentioning
confidence: 99%